Campanularia antarctica Stechow 1922 ... - ÁLVARO L. PEÑA CANTERO (Zenodo, 2017)
Campanularia antarctica Stechow, 1922 (*) Campanularia volubilis var. antarctica Ritchie, 1913: 22 –23, fig. 6. Distribution. Circum-Antarctic (Peña Cantero et al. 2004). In the Ross Sea, known off Cape Royds (Ritchie 1913). ... : Published as part of ÁLVARO L. PEÑA CANTERO, 2017, Benthic hydroids (Cnidaria, Hydrozoa) from the Ross Sea (Antarctica) collected by the New Zealand Antarctic expedition BioRoss 2004 with RV Tangaroa, pp. 1-65 in Zootaxa 4293 (1) on page 26, DOI: 10.11646/zootaxa.4293.1.1, http://zenodo.org/record/828475 ...